An Exploration Into the Sexual Harassment of Hospitality Interns: A Multiple-case Study of the United States, New Zealand and Australia - Zhang, Boyang (Auckland University of Technology, 2020)
Sexual harassment has been considered as a persistent workplace problem in the hospitality industry, and it has been confirmed to influence both employees and organisations negatively. However, previous studies have investigated hospitality employees who experienced sexual harassment in the workplace, however, few have specifically investigated hospitality student interns being harassed sexually. Therefore, this dissertation aims to explore student interns’ experiences of sexual harassment as well as the contextual factors that influence its occurrence in hospitality organisations. It aims to provide suitable recommendations for New Zealand universities to protect their hospitality interns from sexual harassment. The case study research method is adopted in this dissertation, and the United States, New Zealand and Australia have been confirmed as the three case countries. Secondary data were collected from relevant hospitality reports and empirical studies in those countries over a ten-year period. The findings of the study show that, although the dimensions and situations in the three case countries have some differences, there are still several similarities. It concludes that customer-based sexual harassment (harassers are typically customers) appears to be the main manifestation of sexual harassment towards student interns in the hospitality work environment. The findings show that the power imbalance in many hospitality organisations is an important contextual factor influencing the sexual harassment of hospitality interns. Additionally, student interns’ uniforms and sexual harassment-tolerant organisational cultures are significant organisational factors that increase the potential for sexual harassment incidents to occur. In New Zealand, this study pointed that, current protections are inadequate. Based on the three case countries, the findings of this dissertation show that providing training or prior education about sexual harassment for students before internships, providing more targeted online information for students, and train staff members who are identified as the first and initial contact point of contact for students who have experienced sexual harassment can be considered suitable protection methods that will improve the current provisions for vulnerable interns.
Keywords: Sexual harassment; Hospitality interns; Case study; New Zealand; The United States; Australia